Algorithm for Treatment of Supernumerary Nasal Tooth - Souza Santos, Anderson Maikon de [UNESP]; Lima-Neto, Tiburtino Jose de [UNESP]; Mendes, Bruno Coelho [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Sverzut, Alexander Tadeu; Barbosa Luna, Anibal Henrique (Lippincott Williams & Wilkins, 2021)
The presence of a tooth in the nasal cavity is a rare condition. There is an even more rare association, which is the presence with the mineral's deposition and formation of rhinoliths. This report shows a case of rare nasal tooth associated with rhinolithiasis and describes its surgical treatment based on an algorithm. The diagnosis was made by endoscopy with the aid of computed tomography, followed by surgical endoscopy excision. The algorithm and the proposed treatment was successful in its execution and the patient presents no complaints or complications at 3 years after surgery.
Keywords: Nasal cavity; supernumerary tooth; therapeutic